Role of aripiprazole in treatment-resistant schizophrenia - Mossaheb N (Dove Medical Press, 2012)
Nilufar Mossaheb,1 Rainer M Kaufmann21Department of Child and Adolescent Psychiatry, 2Department of Psychiatry and Psychotherapy, Medical University, Vienna, AustriaAbstract: About one third of patients with schizophrenia respond unsatisfactorily to antipsychotic treatment and are termed “treatment-resistant”. Clozapine is still the gold standard in these cases. However, 40%–70% of patients do not improve sufficiently on clozapine either. In the search for more efficacious strategies for treatment-resistant schizophrenia, drugs with different pharmacological profiles seem to raise new hopes, but are they valid? The aim of this review was to evaluate the evidence for aripiprazole as a potential strategy in monotherapy or combination therapy for patients with treatment-resistant schizophrenia. The evidence for aripiprazole monotherapy and for the combination of aripiprazole with psychotropics other than clozapine is scant, and no recommendation can be made on the basis of the currently available data. More effort has been made in describing combinations of aripiprazole and clozapine. Most of the open-label and case studies as well as case reports have shown positive effects of this combination on overall psychopathology and to some extent on negative symptoms. Several reports describe the possibility of dose reduction for clozapine in combination with aripiprazole, a strategy that might help so-called “treatment-intolerant” patients. The findings of four randomized controlled trials with respect to changes in psychopathology seem less conclusive. The most commonly found beneficial effects are better metabolic outcomes and indicators of the possibility of reducing the clozapine dose. However, other side effects, such as akathisia, are repeatedly reported. Further, none of the studies report longer-term outcomes. In the absence of alternatives, polypharmacy is a common strategy in clinical practice. Combining aripiprazole with clozapine in clozapine-resistant or clozapine-intolerant patients seems to be worthy of further investigation from the pharmacological and clinical points of view.Keywords: aripiprazole, clozapine, antipsychotic, treatment-resistant schizophrenia